Beyond fidelity: unveiling the landscape of teacher adaptation in social and emotional learning programs - Lovett, Joshua M.; Schonert-Reichl, Kimberly A.; Zinsser, Katherine M.; Lawlor, Molly S. (Frontiers in Education, 2024)
Despite the rapid growth of social and emotional learning (SEL) programs, research on program implementation has lagged behind. In the landscape of implementation science for SEL programs, fidelity and dosage are often emphasized, but important aspects like adaptation have largely been neglected. This qualitative study addresses three research questions: (1) do teachers make adaptations when implementing SEL programs? (2) how do teachers adapt these lessons? and (3) why do teachers adapt these lessons? Data on adaptation were obtained from 17 elementary and middle school teachers via interviews and open-ended responses from implementation diaries from two randomized controlled trials of SEL programs. Findings revealed that all teachers made at least one adaptation, including structural adaptations (i.e., changes to content, sequencing, and timing) and process adaptations (i.e., adaptations made to how the lesson was delivered and experienced). Teachers also described reasons for adapting that were broadly due to student factors, program factors, and contextual factors. These results shed light on the numerous ways in which teachers adapt SEL programs and the array of complex reasons that lead to the adaptation of lessons within these types of programs and highlight the critical need to consider teacher adaptations in SEL program implementation. Future research should explore the impact of these adaptations on student outcomes and develop robust methods to capture and analyze adaptations.